Detonation and deflagration characteristics of p-Xylene/gaseous hydrocarbon fuels/air mixtures. (15th January 2015) - Zhang, Bo; Xiu, Guangli; Chen, Jian; Yang, Shaopeng
Highlights: New insights into the detonation/deflagration characteristics of p -Xylene/gaseous hydrocarbon fuels/air mixtures. Detonation sensitive of p -Xylene/gaseous hydrocarbon fuels/air mixtures are explored. The relative ease that mixtures can be detonated mainly depend on the detonation sensitive of the gaseous fuels. Abstract: p -Xylene is an important intermediate for the production of polyethylene terephthalate, it has growing chemical industrial demand based on the statistics in the last few decades. In the process of producing p -Xylene, gaseous hydrocarbon fuels (e.g., H2, C1 –C3 ) are usually involved, which renders p -Xylene highly possible mix with those gaseous hydrocarbon fuels as leaking occurs, this presents fire or explosion/detonation hazard at some specific conditions. To date, very limited data regarding its detonation and deflagration characteristics are available in previous literatures. In this study, experiments of measuring the overpressure and velocity of p -Xylene/gaseous hydrocarbon fuels (i.e., H2, C2 H4, C3 H8, CO)/air mixtures are carried out in a vertical detonation tube with an inner diameter of 200 mm and a length of 6.5 m to explore the detonation and deflagration characteristics of p -Xylene. The experimental results indicate that under the same initiation energy of 0.189 MJ m −2, pure p -Xylene/air and p -Xylene/CO/air cannot achieve detonation, only deflagrations are observed. However, under this same initiation energy, detonations occur in p -Xylene/H2 /air, p -Xylene/C2 H4 /air and p -Xylene/C3 H8 /air mixtures. By comparing the combinatorial compositions of p -Xylene along with gaseous hydrocarbon fuels that within which detonation observed, the detonation sensitive of the mixtures in increasing order are obtained as following: p -Xylene/H2 /air, p -Xylene/C3 H8 /air and p -Xylene/C2 H4 /air. The results also indicate the relative ease that p -Xylene/gaseous hydrocarbon fuel/air can be detonated mainly depends on the detonation sensitive of the gaseous fuel, which is supported by the critical energy of direct detonation initiation and chemical kinetic analysis.